Antibacterial efficacy of Acacia nilotica, Aegle marmelos herbal extracts against Enterococcus faecalis: an invitro study - A., Subhashini; Leburu, Ashok; Krishnamurthy, Madhuram; V., Naveen Kumar; Nehrudas , Praveen (International Journal of Research in Medical Sciences, 2023)
Background: Our objective was to evaluate the antibacterial efficacy of Acacia nilotica, Aegle marmelos herbal extracts against Enterococcus faecalis- an invitro study. Methods: The extraction of Acacia nilotica bark powder and Aegle marmelos leaf powder was done with following three solvents (Ethanol, methanol and acetone) keeping vancomycin as a positive control. Then the study groups were assigned as follows: group I: Acacia nilotica, group II: Aegle marmelos, group III: Combination of Acacia nilotica and Aegle marmelos, group IV: vancomycin. Preparation of the E. feacalis inoculum with the help of Mueller Hinton Broth. Antimicrobial efficacy was evaluated by agar well diffusion assay to determine the zone of inhibition and Minimum inhibitory concentration was evaluated. Results: Statistical analysis was performed by using one-way analysis of variance and compared by the Mann-Whitney test using the Statistical Package for the Social Sciences (SPSS) software, version 20.0. No zone of inhibition was identified for Aegle marmelos. Highest inhibitory zone against E. faecalis was seen for vancomycin (mean of 28.6 mm) followed by Acacia nilotica. Conclusions: Among the test groups, vancomycin exhibited highest antimicrobial efficiency. Compared with the herbal extracts which was statistically significant. The use of herbal alternatives might prove to be advantageous considering the several undesirable characteristics of vancomycin.